Safety and Feasibility of Simultaneous Ipsilateral Proximal Carotid Artery Stenting and Cerebral Aneurysm Coiling - Badruddin, Aamir; Teleb, Mohamed S.; Abraham, Michael G.; Taqi, Muhammad A.; Zaidat, Osama O. (Frontiers in Neurology, 2010)
Background: Coexistence of cerebral aneurysm and carotid artery disease may be encountered in clinical practice. Theoretical increase in aneurysmal blood flow may increase risk of rupture if carotid artery disease is treated first. If aneurysm coiling is performed first, stroke risk may increase while repeatedly crossing the diseased artery. It is controversial which disease to treat first, and whether it is safe to treat both simultaneously via endovascular procedures. We document the safety and feasibility of such an approach. Methods: Review of collected neurointerventional database at our institution was performed for patients who underwent both Carotid artery stenting (CAS) and aneurysm coil embolization (ACE) simultaneously. All patients underwent carotid stenting followed by aneurysm coiling in the same setting. Demographic, clinical data and outcome measures including success rate and periprocedural complications were collected. Results: 590 aneurysms coiling were screened for patients who underwent combined CAS and ACE. Ten patients were identified. Mean age was 67.7 years (range 51 to 89). The success rate for stenting and coiling was 100% with no immediate complications. No stroke, TIAs, or aneurysmal rebleeding was found on their most recent follow up. Conclusions: Our case series demonstrates that it is safe and feasible to perform CAS and ACE simultaneously as one procedure which may avoid unwanted risk of treating either disease at two separate time sessions.